Animal production, animal health and food safety: Gaps and challenges in the chilean industry. (October 2018) - Ibarra, R.; Rich, K.M.; Adasme, M.; Kamp, A.; Singer, R.S.; Atlagich, M.; Estrada, C.; Jacob, R.; Zimin-Veselkoff, N.; Escobar-Dodero, J.; Mardones, F.O.
Abstract: This paper summarizes the gaps and challenges related to animal production, health, and food safety as discussed by a panel at the 1st International Symposium of Food Safety (ISFS) in Santiago, Chile, in December 2016. Participating representatives of academia, industry, and government and statements from the audience confirmed that food safety is essential for increasing food security. First, panelists identified the need for a science-based regulatory framework to implement effective regulations. Second, they highlighted the importance of a risk analysis framework to quantify the risk of the potential for antimicrobial resistance associated with the use of antimicrobials, and the need of studies to evaluate foodborne prevention/control strategies. Third, the challenges of filling the gaps between industry and academia were addressed, including examples of successful collaboration, opportunities, and weakness identified by industry. Finally, challenges in animal food production included issues related to changing consumer preferences, animal welfare, the use of antimicrobials, and sustainable animal production. The symposium provided a regional platform to share experiences from the implementation of methods and approaches for food safety. The roundtable successfully explored the future science and technology challenges that are of strategic importance for Chile and the region in animal health and food safety. Highlights: Gaps and challenges in animal production were identified including academia, industry, and government representatives. Issues identified were food safety regulations, the use of antimicrobials, and enhancing industry-academia collaborations. Needs for a regulatory framework including the risk analysis and promoting studies to evaluate prevention/control strategies. Main challenges considered consumer preferences, animal welfare, the use of antimicrobials, and sustainable animal production. This multi-sectorial roundtable was an opportunity to discuss the top-level priorities for forthcoming initiatives.